Cascading of teachers training at higher education in Pakistan: An evaluation of a faculty professional development program. (October 2022) - Iftikhar, Shandana; Fu, Yining; Naureen, Shazia; Cao, Yongguo; Zhou, Chuan
Abstract: Evaluation refers to a systematic collection of data and utilization of that data to improve the program or project. It provides data to judge whether the program attained its goals and to help plan future training. This study aimed to implement an exploratory sequential research framework to evaluate the Master Trainer-Faculty Professional Development Program (MT-FPFP). MT-FPDP was a teachers training program designed for higher education faculty to develop their teaching skills. The current study was divided into two phases. In phase I, qualitative data was collected through document analysis and semi-structured interviews with coordinators of MT-FPDP. A self-developed questionnaire was used for data collection from Master Trainers (MTs) in phase II. Thematic analysis, percentages, and mean scores were used to analyze the data. The findings indicated that exploratory sequential framework was a best fit for evaluating MT-FPD. MT-FPDP was discovered to be a successful university-level teachers' training program. MTs encountered several challenges during the cascade training process at Higher Education Institutions (HEIs). This work contributes to the literature from both an academic and a practical standpoint. First, this study contributes to the literature by implementing exploratory sequential framework as an evaluation design and by providing detailed information regarding the training program's objectives, design, process, implementation, and challenges. Secondly, policy-makers and decision-makers will benefit from the results of the current study. In addition, exploratory sequential framework can aid future evaluators and researchers in systematic evaluations of teachers' training and other programs both inside and outside the education profession. Highlights: An exploratory sequential framework was implemented to evaluate Master Trainers-Faculty Professional Development (MT-FPDP). MT-FPDP was initiated to provide training to a large number of faculty members within a short period. Cascading was a significant component of MT-FPDP. Evaluation of the training program highlighted several challenges obstructing cascading of training at HEIs. This study will be helpful for users interested in evaluating teachers' training or other programs both inside and outside our education.